INDONESIAN CULTURAL DIPLOMACY THROUGH THE PA'GELLU DANCE (TORAJA DANCE) IN JAPAN - Wa Ode Rindang Alamiah (ZILLZELL MEDIA PRIMA, 2024)
This research is about diplomacy effort to introduce Tari Toraja in Japan. Tari Toraja is one of the Indonesian cultures that originates from the land of Toraja, one of the regions in South Sulawesi, Indonesia. This dance is fun dance that is usually performed by Toraja people in traditional events or some important events in Toraja. Tari Toraja is one of the steps to introduce Indonesia cultural to Japan and this research aims to know the efforts of Indonesia diplomacy through Tari Toraja held in Japan. This study uses a neorealist perspective, which focuses on the state as the main actor in the international political system. Indonesia wants to introduce Toraja cultural dance in Japan. To describe this research, the author uses the theory of cultural diplomacy. This research is qualitative, this research uses library research technique, where this research with data collection technique from book literature, magazine, newspaper, and visit to internet and other sources. The results of this study indicate that Indonesia made efforts through multi track diplomacy to introduce Tari Toraja cultural in Japan through multi track Government, Non Government and private citizen, with the effort, Indonesia got the response by Japan community well.